Sertoli-Leydig cell tumour of ovary: a case report - Chand, Arju; Pant, Rajesh (Medical Journal of Shree Birendra Hospital, 2012)
Sertoli–Leydig cell tumor are very rare and make up approximately 0.5% of all ovarian tumors. They typically produce androgen and clinical virilization is present in 70-85% of cases. We report of a Sertoli–Leydig cell tumor without virilization. DOI: http://dx.doi.org/10.3126/mjsbh.v10i2.6462 Medical Journal of Shree Birendra Hospital July-Dec 2011 10(2) 35-37